2009
DOI: 10.1007/978-3-642-03417-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Herd-Based Target Tracking Protocol in Wireless Sensor Networks

Abstract: Abstract. Target tracking is a killer application in wireless sensor networks (WSNs). Energy efficiency is one of the most important design goals for target tracking. In this paper, we propose a herd-based target tracking protocol (HTTP) with the notions of node state transition and herd-based node group for target tracking. A sensor node has three states, namely, sleeping state, sensing state, and tracking state. Each sensor node is associated with a weight to be used to make a state transition among the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…(3) (4) where P(Q[) and P(Q ll) denote the probabilities when the sensor is located in Region I and Region II, respectively; E [C nl] and E [C nlI] denote the corresponding expected coverage of the node. As the nodes are deployed randomly, we get:…”
Section: B Definitionsmentioning
confidence: 99%
“…(3) (4) where P(Q[) and P(Q ll) denote the probabilities when the sensor is located in Region I and Region II, respectively; E [C nl] and E [C nlI] denote the corresponding expected coverage of the node. As the nodes are deployed randomly, we get:…”
Section: B Definitionsmentioning
confidence: 99%
“…LIU Qin [5] utilized binary particle swarm optimization algorithm for tracking multi hiding targets in radar networks. X. Xing [7] depended on three status transport module and put forward a moving target tracking method based on drove, experiment results shown that the solution play a good performance in detection, awakening mechanism and logical networks architecture. The existing solutions have merit and demerit considering detection tracking accuracy and energy consumption roundly.…”
Section: Introductionmentioning
confidence: 99%
“…Another protocol called Herd-Based Target Tracking Protocol (HTTP) is proposed in [53]. It is based on a three state-transition model, namely: sensing, sleeping and tracking.…”
Section: Dynamic Clusteringmentioning
confidence: 99%